Penerapan The Five Canons Rhetoric Aristoteles pada Tayangan Clash of Champions Ruangguru - Mulyanto, Agus; Firmansyah, Arif; Sofwatunisa, Salma; Hidayat, Taufik (ppjbsip, 2025)
This study aims to describe the application of Aristotle's Five Canons of Rhetoric in the show